2012
DOI: 10.5600/mmrr.002.04.a09
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling Medical Expenditure Estimates from the MEPS and NHEA, 2007

Abstract: Objective: Provide a comparison of health care expenditure estimates for 2007 from the Medical Expenditure Panel Survey (MEPS) and the National Health Expenditure Accounts (NHEA). Reconciling these estimates serves two important purposes. First, it is an important quality assurance exercise for improving and ensuring the integrity of each source's estimates. Second, the reconciliation provides a consistent baseline of health expenditure data for policy simulations. Our results assist researchers to adjust MEPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 4 publications
1
73
0
Order By: Relevance
“…Indicator, which was also used for previous chartbooks. 6,16,21 In contrast with the previous chartbook, we did not group 18 and we highlight them so that readers interpret our results with caution.…”
Section: Percentage Of Us Adults Number Of Chronic Conditions Numbementioning
confidence: 87%
“…Indicator, which was also used for previous chartbooks. 6,16,21 In contrast with the previous chartbook, we did not group 18 and we highlight them so that readers interpret our results with caution.…”
Section: Percentage Of Us Adults Number Of Chronic Conditions Numbementioning
confidence: 87%
“…Recall error or imperfect understanding of key questions may mean that some entries may not accurately reflect reality; this may affect the results of this study. For example, other analyses have found that MEPS data tend to underestimate total medical expenditure by about 18 % [47]. This limitation of the dataset would lead to a likely underestimation of the actual cost savings associated with the implementation of primary prevention policies in the USA.…”
Section: Discussionmentioning
confidence: 95%
“…First, we adjusted for the acknowledged level of expenditure differences between MEPS and National Health Expenditure Accounts (NHEA) data, which are widely viewed as a full accounting of national health care expenditures. 7,8 Based on work by Merrile Sing and coauthors, 7 we also inflated expenditures in MEPS by payer category (private insurance, Medicare, Medicaid, and other) to more accurately represent aggregate US medical expenditures as presented in the NHEA. 9 To project uncompensated care costs for 2013, we made two additional adjustments.…”
Section: Study Data and Methodsmentioning
confidence: 99%